18F-FDG PET/CT of Seminal Vesicle Metastasis From Ascending Colon Adenocarcinoma. (February 2017) - Hsu, Yu-Ling; Lin, I-Chen; Tung, Chun-Liang
Abstract : Abstract: The most common metastatic sites of colorectal cancer are the regional lymph nodes, liver, lungs, and peritoneum. Seminal vesicle metastasis from colon adenocarcinoma is not reported yet; the diagnosis could be challenging. We report a case of seminal vesicle metastasis from a primary ascending colon adenocarcinoma in a 49-year-old man, with elevating carcinoembryonic antigen as the only clinical sign. This also highlights the role of 18 F-FDG PET/CT to detect metastatic adenocarcinoma from colon in the genitourinary system.